Youth Perceptions of Friendship Loyalty: Uncovering Psychological Components Through Narratives - Yildiz, Emre; Hoffmann, Clara; Antoniou, Nikos (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to explore how adolescents and young adults perceive and construct the meaning of friendship loyalty, focusing on its emotional, behavioral, and psychological components. Methods and Materials: A qualitative narrative design was employed, involving 21 participants aged 16–24 from Germany. Participants were recruited through purposeful sampling to ensure diversity in age, gender, and educational background. Data were collected using semi-structured interviews, with open-ended questions addressing experiences of trust, betrayal, and support in friendships. Interviews were audio-recorded, transcribed verbatim, and analyzed thematically using NVivo 14 software. Data collection continued until theoretical saturation was reached, ensuring comprehensiveness of the findings. Rigor was enhanced through peer debriefing, audit trails, and reflexive memo writing. Findings: Analysis revealed four main themes: (1) Emotional Foundations of Loyalty (trust, emotional support, belonging, forgiveness, sacrifice, stability, shared joy), (2) Behavioral Expressions of Loyalty (presence in adversity, defense in absence, reciprocity, keeping commitments, protecting vulnerabilities, long-term continuity), (3) Challenges and Breaches of Loyalty (betrayal, neglect, conflicting loyalties, boundary violations, conditional loyalty), and (4) Psychological Outcomes of Loyalty (emotional security, self-worth, resilience, generalized trust, fear of loss, empathy, prosocial motivation). Participants’ narratives emphasized loyalty as both a protective and fragile construct, capable of fostering resilience and self-worth while also producing vulnerability when breached. Conclusion: The findings demonstrate that friendship loyalty among adolescents is a multidimensional phenomenon, deeply embedded in emotional ties, behavioral practices, and developmental outcomes. Loyalty acts as both a stabilizing force and a source of vulnerability, influencing identity, resilience, and trust. These insights underscore the importance of fostering loyal friendships through educational, parental, and community interventions, particularly in an era where digital interactions increasingly shape loyalty norms.